Rational design of Ni-incorporated CuO bifunctional electrocatalyst for sustainable H2 and formate production from biomass - Chuang, Ping-Chang; Lai, Yi-Hsuan (International journal of hydrogen energy, 2025)
The co-production of value-added chemicals and sustainable hydrogen through the electrochemical bio-refinery of cellulosic biomass serves as a promising technology for enabling carbon-neutral cycles. The Ni-incorporated CuO, prepared by simple solution-based synthesis, was rationally designed for efficient and selective formate (FA) production from electrocatalytic cellulosic biomass valorization. With Ni incorporation, the Fermi level of CuO shifts toward a more negative potential, resulting in the free hole injection into the electrolyte at a less positive potential and, thereby, a lower operation potential for electrocatalytic FA production compared to CuO. Among a series of compositions, the CuO with 16 % Ni incorporation (CuNiOx r = 0.16) exhibits the most promising electrocatalytic activity toward selective FA production from glucose with a turnover frequency of 207 ± 23 h−1 at 1.4 V vs. reversible hydrogen electrode, much higher than that of CuO (117 ± 7 h−1). Notably, CuNiOx also acts as an effective precatalyst for the hydrogen evolution reaction, which could be converted into a Cu/NiO hydrogen evolution catalyst under cathodic conditions. The cathodically treated CuNiOx r = 0.16 (CuNiOx r = 0.16 red.) has a much smaller overpotential of 197 mV at 10 mA cm−2 compared to that of cathodically treated CuO (468 mV). A solar-driven electrochemical glucose valorization system for the co-production of green hydrogen and FA was successfully constructed by pairing CuNiOx r = 0.16 and CuNiOx r = 0.16 red. in a two-electrode flow system. This work shows that the band structure of electrocatalysts is also an inescapable consideration for designing effective electrocatalysts for biomass valorization. [Display omitted] •A simple, scalable process of CuNiOx for various substrates is demonstrated.•Ni-incorporated CuO exhibits notable activity for glucose oxidation.•The role of Ni in the electrocatalytic activity of CuNiOx is revealed.•CuNiOx shows promising H2 production activity via an in-situ formation of Cu/NiO.•A solar flow system for the selective production of formate and H2 is demonstrated.